2017
DOI: 10.18632/oncotarget.18456
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of differences in Constant-Murley scores for three mid-shaft clavicular fracture treatments

Abstract: There is no consensus on the optimal treatment for mid-shaft clavicular fracture. We conducted a meta-analysis to compare the effectiveness of non-operative treatment, plate fixation, and intramedullary pin fixation in terms of the Constant-Murley Score (CMS) for treatment of mid-shaft clavicular fracture. Comprehensive search of the Embase, Cochrane Library and PubMed was conducted to retrieve relevant randomized controlled trials (RCTs). A random-effect network meta-analysis was conducted within a Bayesian f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Jiang et al 20 compared nonoperative measures, plate, and intramedullary pin fixation in a meta-analysis. They observed that there were no differences in the effectiveness assessed by the CMS at six weeks, three, 12, and 24 months, and suggested that intramedullary pin fixation might be the optimal therapeutic approach.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al 20 compared nonoperative measures, plate, and intramedullary pin fixation in a meta-analysis. They observed that there were no differences in the effectiveness assessed by the CMS at six weeks, three, 12, and 24 months, and suggested that intramedullary pin fixation might be the optimal therapeutic approach.…”
Section: Resultsmentioning
confidence: 99%